THE ROLE OF HISTORICAL ANALOGIES IN FOREIGN POLICY - Jurgelevičiūtė, Diana (Politologija, 2015)
This article asks the question, how foreign policy is explained by analyzing historical analogies that are voiced by policymakers? There had been attempts to answer this question already. In general four approaches based on the role of historical analogies they see can be outlined: instrumental, cognitive, cognitive-instrumental and constitutive. However a review of conventional approaches revealed their limits and questions that they ignore. None of the conventional approaches has a theoretical explanation of how policymakers use historical analogies in order to show differences between past and present events that they compare. None of the conventional approaches can explain the role of historical analogies in constituting rule-based context that governs actions of actors. Instrumental and cognitive approaches are not interested in consequences of historical analogy use. Instrumental, cognitive and cognitive-instrumental approaches do not explain constitutive role of the use of historical analogy.This article presents an alternative explanation of how and why policymakers use historical analogies and develops new model for analysis of historical analogies. It enables answering all of the above mentioned questions that conventional approaches can not. The model is based on the assumptions of rule-oriented constructivism, speech act theory and includes dialogical analysis method. Based on speech act theory use of language and in this case – use of historical analogy is a form of action. Historical analogy is not a simple comparison of past and present events but it is a comparison of what is perceived as social rules of the past and the present. Based on rule-oriented constructivism theoretical question how historical analogies construct social rules is answered. With dialogical analysis method empirical question how historical analogies construct social rules is answered.It is argued that historical analogies play two roles in foreign policy decision-making stage. First role is cognitive – policymakers use historical analogies in order to understand foreign policy issues with the help of intersubjective rules that are linked with particular past or present events. Second role is constitutive – foreign policy context, identities and interests of actors are constituted by giving them meanings that are related with particular rules of the past or present events.The role of historical analogies in foreign policy implementation stage is to construct rule-based context in which foreign policy takes place. This is not an individual action as the constitutive role of historical analogies may imply. Construction of rule-based context is a collective process that involves interaction between actors who use historical analogies and actors that are described by those historical analogies. Thus in order to explain foreign policy one needs to identify rules that actors follow and constitute. Thus the question, how foreign policy is explained by analyzing historical analogies, can be answered by identifying what type of rules and context are emerging out of interaction between policymakers who use historical analogies.